Investigating isocitrate dehydrogenase mutations in cancer using new metabolomics methods - Walsby-Tickle, J (2020)
Altered cellular metabolism, as a result of oncogenic mutations, has been observed in a range of cancer types. A detailed understanding of how cancers modify cellular metabolism, which includes changes to the genome, proteome and metabolome, is therefore integral for the development of effective and targeted therapeutic treatments.